Autoimmune Antiphospholipid Antibodies Are Directed against a Cryptic Epitope Expressed when β2-Glycoprotein I Is Bound to a Suitable Surface - Pengo, Vittorio; Biasiolo, Alessandra; Fior, Maria Grazia (Thrombosis and Haemostasis, 1995)
The antiphospholipid antibodies (aPL) present in autoimmune disorders are associated with thromboembolic episodes, and their binding to phospholipids (PL) is mediated by a plasma cofactor, β2-glycoprotein I (β2GPI). Both PL and β2GPI seem necessary for binding, thus indicating that the two components comprise the epitope against which aPL are directed. Using an anti-β2GPI antibody ELISA with the antigen adsorbed onto polyvinylchloride (PVC) plates, we detected high antibody titres in 12 out of 12 plasmas from patients with the antiphospholipid syndrome. No or very low positivity was obtained when the same ELISA was carried out in polystyrene (PST) plates, while an increasing positivity was found when processed (i.e. more hydrophilic) or COOH-surface PST plates were used. When (β2GPI dependent IgG-aPL were purified using agarose-immobilized cardio- lipin, 4 out of 4 preparations were highly positive in anti-β2GPI antibody ELISA using PVC plates, while β2GPI was not fully recognized by aPL-IgG when adsorbed onto PST plates. These findings demonstrate that aPL are, in fact, anti-β2GPI antibodies directed against a cryptic epitope which is expressed when β2GPI is bound to anionic phospholipid, or another suitable surface.